2005
DOI: 10.1103/physrevb.72.172410
|View full text |Cite
|
Sign up to set email alerts
|

Spin dynamics of magnetic nanoparticles: Beyond Brown’s theory

Abstract: An investigation of thermally induced spin dynamics of magnetic nanoparticles is presented. We use an atomistic model for the magnetic interactions within an effective, classical spin Hamiltonian constructed on the basis of first-principles calculations for L1 0 FePt. Using Langevin dynamics we investigate how the internal degrees of freedom affect the switching behavior at elevated temperatures. We find significant deviations from a single-spin model, arising from the temperature dependence of the intrinsic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 25 publications
2
65
0
Order By: Relevance
“…K is the anisotropy energy per atom, i.e., the energy barrier to reversal for a single atom, equal to equal to the quantum threshold given by Eq. (13). Note that this threshold is independent of the number of atoms in the magnetic object.…”
Section: A Effect Of the Longitudinal Anisotropy ( D = 0 E = 0)mentioning
confidence: 96%
See 1 more Smart Citation
“…K is the anisotropy energy per atom, i.e., the energy barrier to reversal for a single atom, equal to equal to the quantum threshold given by Eq. (13). Note that this threshold is independent of the number of atoms in the magnetic object.…”
Section: A Effect Of the Longitudinal Anisotropy ( D = 0 E = 0)mentioning
confidence: 96%
“…The development of spin-polarized scanning tunneling microscopy (SP-STM) led to detailed observations of the thermally induced magnetic switch in small ferromagnets, allowing a detailed test of the global rotation of the Néel-Brown view and of its limits. [3][4][5][6][7][8][9][10] In parallel, analyses led to the discussion of other views of the thermally activated magnetization switch, [10][11][12][13][14][15][16][17] for example, spin-wave contributions, nucleation, edge effects, and anisotropy effect. Following earlier works on multilayered materials, 18,19 SP-STM experiments revealed that injection of spin-polarized electrons into a nanoferromagnet could also switch its magnetization.…”
Section: Introductionmentioning
confidence: 99%
“…Two further models that connect to the transport properties, a shift of the chemical potential Similar to micromagnetic models gaining high predictive power and becoming an indispensable tool for nanomagnetism 112 in the last decade, thermal models, meanwhile, reach predictive power for ultrafast experiments. 113 For example, it will be possible to optimize writing asymmetries in all-optical writing experiments to reduce fluence thresholds in the future. The role of spin wave or spin-cluster fluctuations in the characteristic response of the ferromagnet has been suggested in early 2007 in parallel by different groups by atomistic, 114 thermal macrospin, 115,116 or simple micromagnetic spin-fluctuation 117 models.…”
Section: Theoretical Perspectivesmentioning
confidence: 99%
“…In the former, a suitable simplification of the exchange interaction in a magnetic solid is to express it through the Heisenberg Hamiltonian H xc = − α>β J αβ S α · S β , where the J αβ are exchange constants and S α is the atomic spin on atom α. Using this Hamiltonian to express the exchange field leads to LandauLifshitz-Gilbert equations of motion for the dynamics of atomic moments (see, e.g., [74][75][76]). …”
Section: Exchange Field and Nonlocal Contributionsmentioning
confidence: 99%